A Study of the Effect of Different Thermal Treatments on the Characteristics of Quality and Storage Duration of a Drink Made from Cheese Whey and Orange Juice - Aldarf, Ruba; Sultanah, Ali; Harfosh , Mohsen (Latakia University Journal -Biological Sciences Series, 2013)
The main aim of the research is to conduct several thermal treatments and to study their effects on the physical, chemical and microbiocal properties of a drink made from 50% cheese whey and 50% orange juice during cold storage. The thermal treatments conducted were: 72 Cº for 40 seconds, 85 Cº for 20 seconds, 100 Cº for 15 seconds, and 80 Cº for 15 minutes. The storage durations were 2 weeks for the first treatment, 5 weeks for the third treatment, and 3 weeks for the second and fourth treatments. The effects of these treatments on titratable acidity, pH, total soluble solids, turbidity, viscosity and degree of separation were studied and evaluated during storage. The acidity and total soluble solids increased slightly during storage; the pH value decreased in all thermal treatments; and the degree of separation, viscosity and turbidity was the lowest with the thermal treatment of 80 Cº for 15 minutes. This gave an advantage to this treatment as it provides higher stability and better acceptability of the drink by the consumer. During the different periods of storage, all drink samples showed good microbiocal properties and were in conformity with the Syrian food standard specifications.